WORD PICTURES OF THE ENVIRONMENT AND INTERIOR IN SAYAKA MURATA'S I-NOVEL "CONVENIENCE STORE WOMAN" (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
In this article the artistic images of the environment and interior and their features are shown in modern Japanese I-novels using the example of Sayaka Murata's work called "Convenience Store Woman". The novel is also interesting because through the prism of the interiors of shops, modern Tokyo, we are introduced to the system of shopping services in minimarkets in Japan, as well as some relationships in the Japanese family and society.